Caring for the 'Holy Land' : Filipina domestic workers in Israel - Liebelt, Claudia (EASA series, 2011)
In Israel, as in numerous countries of the global North, Filipina women have been recruited in large numbers for domestic work, typically as live-in caregivers for the elderly. The case of Israel is unique in that the country has a special significance as the 'Holy Land' for the predominantly devout Christian Filipina women and is at the center of an often violent conflict, which affects Filipinos in many ways. In the literature, migrant domestic workers are often described as being subject to racial discrimination, labour exploitation and exclusion from mainstream society. Here, the author pr.